THE INFLUENCE OF ONLINE LEARNING VIA WHATSAPP ON STUDENTS’ LEARNING MOTIVATION IN PMKR SUBJECT - Subagja, Rizky Eka; Suherman, Amay; Sukrawan, Yusep (Universitas Pendidikan Indonesia, 2021)
Online learning as a concept certainly has several variables, one of which is student learning motivation. This study aims to determine how much influence caused by online learning via WhatsApp on students' learning motivation and to find out whether online learning has a significant effect and has a positive or negative relationship on students' learning motivation. The author raised the topic of this study after conducting a survey to 15 students and seeing the facts in the form of learning outcomes which indicated a lack of student motivation in online learning. The design of this study used a mix method approach. Data collection techniques use a questionnaire, observation, interview and data analysis using simple linear regression analysis. The results showed that online learning via WhatsApp had a significant influence and had a positive relationship on students' learning motivation, as well as an influence of 55,7% on students' learning motivation, 60.6% on students' desire to carry out learning activities, 30.4% on students' interest in learning activities, 25.7% on encouragement of students to carry out learning activities, 15.2% of the needs of students to carry out learning activities, 8.2% of the students' expectations to achieve their goals, 17.6% of students' desire to achieve their goals, 28.8% of self respect, 18.7% to the attractiveness of learning activities, by 28.3% to the conduciveness of the learning environment.